"Against the silence": Development and first results of a patient survey to assess experiences of safety-related events in hospital - Schwappach David LB (BMC, 2008)
Abstract Background Involvement of patients in the detection and prevention of safety related events and medical errors have been widely recommended. However, it has also been questioned whether patients at large are willing and able to identify safety-related events in their care. The aim of this study was to develop and pilot test a brief patient safety survey applicable to inpatient care in Swiss hospitals. Methods A survey instrument was developed in an iterative procedure. The instrument asks patients to report whether they have experienced specific undesirable events during their hospital stay. The preliminary version was developed together with experts and tested in focus groups with patients. The adapted survey instrument was pilot-tested in random samples of patients of two Swiss hospitals (n = 400). Responders to the survey that had reported experience of any incident were sampled for qualitative interviews (n = 18). Based on the interview, the researcher classified the reported incidents as confirmed or discarded. Results The survey was generally well accepted in the focus groups and interviews. In the quantitative pilot test, 125 patients returned the survey (response rate: 31%). The mean age of responders was 55 years (range 17-91, SD 18 years) and 62.5% were female. The 125 participating patients reported 94 "definitive" and 34 "uncertain" events. 14% of the patients rated any of the experienced events as "serious". The definitive and uncertain events reported with highest frequency were phlebitis, missing hand hygiene, allergic drug reaction, unavailability of documents, and infection. 23% of patients reported some or serious concerns about their safety. The qualitative interviews indicate that both, the extent of patients' uncertainty in the classification of events and the likelihood of confirmation by the interviewer vary very much by type of incident. Unexpectedly, many patients reported problems and incidents related to food and dietary intake. Overall, the in-depth interviews confirmed experiences from the focus groups that many patients feel reluctant to report undesirable events without acknowledging the presence or absence of individual responsibility or failure. Many patients reported that they did not ask or communicate about errors or near misses with staff and some patients even develop strategies to improve their safety but do not disclose these to staff. Conclusion Many patients experience undesirable events during hospitalization and a significant number of patients is seriously concerned about their safety. Surveying patients about experiences with safety-related events in hospital seems a valuable tool for identifying and monitoring problematic areas of care and undesirable events. Evidence from the qualitative interviews indicates that safety remains an unsaid word between patients and their care providers.